Contemporary Issues and Challenges in Southeast Asia - Anggun Tyas Jati Dewi; Aprillia Ripanti; Intan Dwi Cahya (The Future of Education Journal, 2026)
This research examines the development of actual issues in Southeast Asia which is now centered on the vulnerability of food security, territorial disputes in the South China Sea, and the challenges of socio-economic integration in the 2026 digital era. The main focus of the research is to evaluate the effectiveness of ASEAN diplomacy in mitigating internal and external conflicts that threaten regional stability. By applying qualitative methods through document studies and discourse analysis of the latest policies of member countries, the research results show that although economic growth begins to stabilize, inequality in access to technology and non-traditional security threats such as cyber attacks and transnational crime become serious obstacles. In addition, ASEAN's bargaining position is tested in maintaining neutrality in the midst of increasingly sharp global power polarization. In conclusion, Southeast Asia requires a more assertive leadership paradigm transformation and closer cross-border policy synchronization to ensure the region remains competitive and peaceful in the face of volatile global dynamics.